Co-integration Between Sensex and Other Popular Indices: A Decadal Study. Issue 2 (June 2019) - Bhatia, Parul; Ramasubramanian, Hemalatha
Abstract: We examine the inter-relationship between India, the USA, Japan, China, France, Dubai and Germany using multivariate co-integration techniques. The study has investigated co-movements between these world indices from 2009 to 2018. During this period, it was found using Johansen co-integration that these indices were co-integrated in the long run. However, in the vector error correction model, long-run causality could not be found. Thereafter with Wald-χ 2 diagnostics, it was found that short-run linkages existed among Indian and rest of the world markets in the study. Therefore, the seven indices may be concluded to have causal relationship in the short run and co-integrating association in the long run.